Heidegger: theology as a positive science - Emelianenko, Anna (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2014)
The article examines the religious foundation of philosophical thought of Martin Heidegger and its relation to theology, in particular, Heidegger’s definition of theology as ontic, positive science. Observed variability and ambiguity of interpretation interdependence between philosophy and theology, which is defined ambiguous and contradictory concept of the German thinker